Geoscience of Climate and Energy 12. Water Quality Issues in the Oil Sands Region of the Lower Athabasca River, Alberta - Schindler, David W. (Geoscience Canada, 2013)
I summarize the controversies about industrial pollutants in freshwaters near the oil sands industrial area of Alberta, the inadequacies in environmental monitoring that have led to widespread misconceptions, and recent attempts to correct the problems. Adequate data are available to show that mercury, other trace metals, and polycyclic aromatic compounds are being added by industry to the Athabasca river system and its watershed, although the relative contributions of industrial development and natural sources remain in question. Recent improvements in water monitoring by Environment Canada show promise of resolving the controversies, although independent governance for Canada’s and Alberta’s water monitoring programs in the lower Athabasca River will be necessary to rebuild public confidence in the data and their interpretation by government and industry. I document one success story in the Athabasca River: the elimination of dioxins from pulp mills in the mid-1990s has caused a consumption advisory for fish in the river to be repealed. SOMMAIRE Je présente ci-dessous un résumé des controverses concernant les polluants industriels dans les eaux douces à proximité de la zone industrielle des sables bitumineux de l’Alberta, des lacunes dans la surveillance des milieux de vie à l’origine d’idées fausses répandues, et de récentes tentatives visant à corriger les problèmes. Des données adéquates démontrent que l’industrie ajoute du mercure et d’autres métaux traces ainsi que des composés aromatiques polycycliques dans le système fluvial de la rivière Athabasca et dans son bassin versant, bien que les contributions relatives provenant de ces activités industrielles et de sources naturelles demeurent toujours en litige. De récentes améliorations apportées au contrôle des eaux par Environnement Canada permettent d’espérer une résolution des controverses, mais l’application d’une gouvernance indépendante des programmes de contrôle de l’eau de l’Alberta du Canada dans la partie inférieure du fleuve Athabasca sera nécessaire pour rétablir la confiance de la population à l’égard des données présentées et de leur interprétation par le gouvernement et l’industrie. Je décrie l’histoire d’une intervention réussie dans la rivière Athabasca, soit l’élimination de dioxines provenant des usines de pâte du milieu des années 1990 et qui a abouti à l’abrogation d’un avis de limitation de la consommation de poisson dans la rivière. DOI: http://dx.doi.org/10.12789/geocanj.2013.40.012